Polymer-Based Biomaterials and Tissue Engineering - Sabater i Serra, Roser; Serrano-Aroca, Ángel (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Polymers in the form of films, fibers, nano- and microspheres, composites, and porous supports are promising biomaterials for a wide range of advanced biomedical applications. This Special Issue presents novel studies and new approaches in the field of biomaterials for tissue engineering and drug delivery. It includes seven original research articles and two reviews on biomaterials based on polymeric matrices with various structures, including porous composites, nanofibrous scaffolds, meshes, and hydrogels, which can include micro- or nanoparticles (graphene nanosheets, bioactive glass, and hydroxyapatite and halloysite nanotubes).